Overlapping patterns of neural activity for different forms of novelty in fMRI - Hawco, Colin; Lepage, Martin (Frontiers in Human Neuroscience, 2014)
When stimuli are presented multiple times, the neural response to repeated stimuli is reduced relative to novel stimuli (repetition suppression). Responses to different types of novelty were examined. Stimulus novelty was examined by contrasting first vs. second presentation of triads of objects during memory encoding. Semantic novelty was contrasted by comparing unrelated (semantically novel) triads of objects to triads in which all three objects were related (e.g. all objects were tools). In recognition, associative novelty was examined by contrasting rearranged triads (previously seen objects in a new association) with intact triads. Activity was observed in posterior regions (occipital and fusiform), with the largest extent of activity for stimulus novelty and smallest for associational novelty. Frontal activity was also observed in stimulus and semantic novelty. Additional analysis indicated that the hemodynamic response in voxels identified in the stimulus and semantic novelty contrasts was modulated by reaction time on a trial-by-trial basis. That is, the duration of the hemodynamic response was driven by reaction time. This was not the case for associative novelty. The high level of overlap across different forms of novelty suggests a similar mechanism for reduced neural activity, which may be related to reduced visual processing time. This is consistent with a facilitation model of repetition suppression, which posits a reduced peak and duration of neuronal firing for repeated stimuli.